Survey of some aspects of artisanal fisheries of Sabiyel lake, Aliero, Kebbi state, Nigeria (Research in Agriculture Livestock and Fisheries, 2015)
A survey was conducted to assess some aspects of artisanal fisheries in fishing households of Sabiyel Lake in Aliero local Government Area, Kebbi State, Nigeria between 2014 and 2015. One hundred (100) questionnaires were administered in seven (7) communities surrounding the Lake. Data was analyzed using descriptive statistics. Results revealed that 100% of the sampled households were married. The age of the respondents vary with 43% below the age of 50, 32% above 50 years of age. All of the households sampled were male. Respondents with no formal education accounted for 77%. Majority of the respondents still use traditional gears, methods and crafts. Most respondents (53%) were involved in only selling of fresh product as a means of livelihood. The fish species caught in Sabiyel lake comprises of Hyperopesus bebe, Oreochromis niloticus, Sarotherodon galilieus, Clarias gariepinus and Heterotis niloticus. Most respondents (42%) sold their fish fresh without processing or preservation. Regarding the role of women, 28% of the respondents mentioned that women participate in the processing of fish. Most of the respondents (87%) stated lack of both modern fishing gears and crafts as the major problems confronting their fishing activities. The study suggested that state government should address the major constraints to fishing in the study area by supplying and subsidizing fishing gears, crafts and adequate processing and preservation equipment.Res. Agric., Livest. Fish.2(3): 507-515, December 2015